HUBUNGAN INDEKS MASSA TUBUH (IMT) DAN POLA KONSUMSI ASAM LEMAK OMEGA-3 TERHADAP KADAR KOLESTEROL TOTAL PADA PEGAWAI DI YOGYAKARTA - Alfi Nur'aini; Adhila Fayasari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Office workers with a sedentary lifestyle are at risk of elevated total cholesterol levels. Excess Body Mass Index (BMI) and low omega-3 intake have the potential to affect lipid balance in the blood. Omega-3 intake plays an important role in maintaining normal lipid profiles and reducing the risk of cardiovascular diseases. Objectives: This study aimed to determine the relationship between Body Mass Index (BMI) and omega-3 fatty acid intake patterns with total cholesterol levels among employees in Yogyakarta. Methods: This research employed a cross-sectional design with a total of 158 respondents selected through purposive sampling. Data were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), height and weight measurements, and cholesterol level examination using a cholesterol meter. Statistical analyses used were the Spearman rank test and Chi-square test. Results: The majority of respondents had high total cholesterol levels (63.9%), excessive BMI (70.3%), and low omega-3 intake (78.5%). There was no significant relationship between BMI and total cholesterol levels (p=0.560). However, there was a significant relationship between omega-3 intake and total cholesterol levels (p=0.024; OR=2.25), indicating that respondents with low omega-3 intake had a 2.25 times higher risk of having high cholesterol levels. Conclusion: There was no significant relationship between BMI and total cholesterol levels among employees in Yogyakarta. However, there was a significant relationship between omega-3 intake and total cholesterol levels. These findings highlight the importance of increasing omega-3 intake as a preventive measure against dyslipidemia in office workers.Keywords : BMI; omega-3; office workers; total cholesterol ABSTRAKLatar belakang: Pegawai perkantoran dengan gaya hidup sedentari berisiko mengalami peningkatan kadar kolesterol total dalam darah. Indeks Massa Tubuh (IMT) yang berlebih dan pola konsumsi omega-3 yang rendah berpotensi dapat mempengaruhi keseimbangan kadar lipid dalam darah. Asupan omega-3 berperan penting dalam menjaga profil lipid tetap normal dan menurunkan risiko penyakit kardiovaskular. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara Indeks Massa Tubuh (IMT) dan pola konsumsi asam lemak omega-3 terhadap kadar kolesterol total pada pegawai di Yogyakarta. Metode: Penelitian ini menggunakan desain cross sectional dengan jumlah responden 158 orang yang dipilih secara purposive sampling. Data dikumpulkan menggunakan kuesioner Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), pengukuran tinggi badan dan berat badan, serta pemeriksaan kolesterol dengan alat cholesterol meter. Analisis statistik yang digunakan yaitu uji spearman-rank dan chi-square. Hasil: Sebagian besar responden memiliki kadar kolesterol total tinggi (63,9%), IMT berlebih (70,3%), dan pola konsumsi omega-3 rendah (78.5%). Tidak terdapat hubungan yang signifikan antara IMT dan kadar kolesterol total (p=0,560). Terdapat hubungan yang signifikan antara pola konsumsi omega-3 dan kadar kolesterol total (p=0,024; OR=2,25), menunjukkan bahwa responden dengan asupan omega-3 yang kurang memiliki risiko 2,25 kali lebih besar memiliki kolesterol tinggi. Simpulan: Tidak terdapat hubungan antara IMT dan kadar kolesterol total pada pegawai di Yogyakarta. Terdapat hubungan antara pola konsumsi omega-3 dan kadar kolesterol total pada pegawai di Yogyakarta. Hasil ini menunjukkan pentingnya peningkatan konsumsi omega-3 sebagai upaya pencegahan terhadap dislipidemia pada pegawai kantoran.Kata Kunci : IMT; kolesterol total; omega-3; pegawai kantoran